RUTMath – a Free and Open-Source Educational Application for Learning Mathematics - Mariusz BORKOWSKI; Dariusz KROL; Piotr KROL; Arkadiusz POLEC; Wojciech WEGRZYN (Communications of International Proceedings, 2025)
The aim of this work is to present an open-source, cross-platform educational application designed to support the acquisition of mathematical skills by early school-age children. The tool combines classical arithmetic exercises (addition, multiplication, multiplication tables, unit conversion) with gamification elements such as duel mode and a reward system. The application is based on the principles of the Singapore method, fostering the development of mathematical competence through visualizations and an intuitive interface adapted to the perceptual abilities of young users. It operates fully offline and does not store data in the cloud, which enhances both its accessibility and security. The project’s source code is available on the GitHub platform, while distribution is carried out via the F-Droid repository. Released under the GPLv3 license, the application supports the idea of free software, and its multilingual support enables global application in the field of education. The project also constitutes an element of the promotional strategy of the Rzeszów University of Technology, emphasizing its commitment to social engagement, openness, and innovation.
Keywords: Mobile learning; educational technology; open-source software